Ulf Hannerz: Cultural Complexity: Studies in Social Organization of Meaning - Henriques, Peter (Tidsskriftet Antropologi, 1993)
Ulf Hannerz: Cultural Complexity: Studies in Social Organization of Meaning Anmeldes af Peter Henriques